Photocatalytic Reduction of Methylene Blue by Surface-Engineered Recombinant Escherichia coli as a Whole-Cell Biocatalyst - Ashokkumar Kumaravel; Vidhya Selvamani; Soon Ho Hong (Bioengineering, 2023)
A novel Escherichia coli strain, created by engineering its cell surface with a cobalt-binding peptide CP1, was investigated in this study. The recombinant strain, pBAD30-YiaT-CP1, was structurally modeled to determine its cobalt-binding affinity. Furthermore, the effectiveness and specificity of pBAD30-CP1 in adsorbing and extracting cobalt from artificial wastewater polluted with the metal were investigated. The modified cells were subjected to cobalt concentrations (0.25 mM to 1 mM) and pH levels (pH 3, 5, 7, and 9). When exposed to a pH of 7 and a cobalt concentration of 1 mM, the pBAD30-CP1 strain had the best cobalt recovery efficiency, measuring 1468 mol/g DCW (Dry Cell Weight). Furthermore, pBAD30-CP1 had a higher affinity for cobalt than nickel and manganese. Field Emission Scanning Electron Microscopy (FE-SEM), Transmission Electron Microscopy (TEM), and Energy-Dispersive X-ray Spectroscopy (EDS) were used to examine the physiochemical parameters of the recombinant cells after cobalt adsorption. These approaches revealed the presence of cobalt in a bound state on the cell surface in the form of nanoparticles. In addition, the cobalt-binding recombinant strains were used in the photocatalytic reduction of methylene blue, which resulted in a 59.52% drop in the observed percentage. This study shows that modified E. coli strains have the potential for efficient cobalt recovery and application in environmental remediation operations.